Releasing the Smile: Depressor Anguli Oris Excision in the Context of Managing Nonflaccid Facial Palsy. Issue 2 (25th January 2022) - Derakhshan, Adeeb; Miller, Matthew Q.; Malka, Ronit; Gadkaree, Shekhar K.; Hadlock, Tessa A.
Abstract : Background: Nonflaccid facial palsy is a debilitating entity characterized by hypertonicity, synkinesis, and hypomobility. Patients with nonflaccid facial palsy often have smile asymmetry and restriction because of disruption of normal vector forces on the modiolus. Excision of the depressor anguli oris can lead to improved oral commissure excursion, smile angle, dental show, and symmetry. Methods: All depressor anguli oris resection cases between January 8, 2018, and December 26, 2019, were reviewed. Patients with postoperative photographs were included in this cohort study. Preoperative and postoperative photographs were analyzed using the Emotrics software program, and changes in oral commissure excursion, smile angle, and dental show were tracked. Clinician-graded facial palsy assessments and patient-reported outcome measures were compared preoperatively and postoperatively using the Electronic Facial Paralysis Assessment and Facial Clinimetric Evaluation Scale, respectively. Results: Forty-three patients were included in this study; 79 percent of patients underwent isolated depressor anguli oris resection. Depressor anguli oris resection led to a statistically significant increase in oral commissure median excursion, smile angle, and dental show [3.02 mm ( p = 0.015), 1.70 degrees ( p = 0.002), and 2.36 mm ( p < 0.001), respectively]. Median Electronic Facial Paralysis Assessment and Facial Clinimetric Evaluation Scale instrument scores also improved [6.0 ( p = 0.001) and 7.5 ( p = 0.013), respectively]. Depressor anguli oris resection also led to more symmetric smiles. No correlation was seen between duration of follow-up and change in metrics. Conclusion: Depressor anguli oris resection is a minimal-risk procedure that frequently results in improved smile dynamics, smile symmetry, and quality of life in patients with nonflaccid facial palsy. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.